Insulin-like Growth Factor-1 and Myocardial Remodeling in Patients with Chronic Heart Failure of Ischemic Origin - A. N. Zakirova; N. E. Zakirova; D. F. Nizamova (Столичная издательская компания, 2022)
Aim. To study the presence and nature of correlations between the level of Insulin-like growth factor-1 (IGF-1) and structural and functional parameters of the heart in the development of myocardial remodeling and fibrosis in patients with chronic heart failure (CHF) of ischemic origin.Material and methods. The study included 120 men with class II-IV CHF who have history of myocardial infarction, which are divided into 3 groups depending on the CHF class. The control group included 25 healthy men. Assessment of left ventricular (LV) structural-functional state was carried out by echocardiography. Investigation of IGF-1 and N-terminal precursor indices of cerebral natriuretic peptide (NT-pro BNP) was performed by enzyme immunoassay.Results. Patients with class II CHF were hyperexpression of IGF-1, with class III CHF were registered low-normal level, with class IV CHF was established a deficiency of IGF-1. The most significant structural-geometric rearrangement of LV and significant deficit of IGF-1 recorded in patients with class IV CHF (95,6±7,02 ng/ml with class IV CHF versus 178,3±11,36 ng/ml and 124,3±9,14 ng/ml with class II and III CHF; р<0,05). In patients of class III-IV CHF, correlation relationships between IGF-1 level and echocardiographic parameters (LV myocardial mass index are established: r=-0,59, p=0,05; end systolic volume index: r=-0,55, p=0,05; value of LV ejection fraction: r=0,61, p=0,05). Significant negative correlation are established in patients with class III-IV CHF between IGF-1 level and NT-pro BNP levels (r=-0,51; р=0,05).Conclusion. The intensity of myocardial remodeling and fibrosis processes in patients with a progressive course of CHF is related to deficit of IGF-1 and is associated with a high level of activity of natriuretic peptides.